La utilización de la auditoría forense como mecanismo para evitar fraudes y errores en las agencias de carga aérea del Distrito Metropolitano de Quito en los ejercicios económicos 2012 y 2013 - López Villacis, Juan Pablo (2015)
This research provides information about the implementation of the Forensic Audit as a technique to prevent and detect fraud and error in air cargo agency of Quito city during 2012 and 2013. This investigation is aimed at professionals who want to start your knowledge and have a new perspective on this efficient control model. For the development of the research, It was performed an interview and a survey that were applied to each of the 24 companies that conform the sample; these were answered jointly by different partners such as financial managers, heads of audit (or internal control), accountants, IT, operations and payroll personnel. The project consists in five chapters, the firsts provide the reader, general ideas and criteria relating to the theme. The first one covers the conceptual framework of the forensic audit, its causes and origins, definitions, objectives, phases and techniques applied. Chapter two provides information within the business line relating to air cargo agency, concepts, terms negotiation, guilds and control agencies. The following chapters show the research methods applied in the project, based in the analysis of questions asked by the survey and how the conjunction of them help us to establish the application of the techniques of Forensic Audit. Finally, the last chapter presents the conclusions and recommendations obtained which constitute our contribution.